Crystal structure of (1,4,8,11-tetraazacyclotetradecane-κ4N,N′,N″,N‴)palladium(II) tetraiodidopalladate(II), C10H24I4N4Pd2 - Ha Kwang (Zeitschrift für Kristallographie - New Crystal Structures)
C10H24I4N4Pd2, monoclinic, P21/n (no. 14), a = 8.955(7) Å, b = 15.587(13) Å, c = 14.752(12) Å, β = 95.63(2)°, V = 2049(3) Å3, Z = 4, Rgt(F) = 0.0564, wRref(F2) = 0.1562, T = 223 K.